PENINGKATAN PERKEMBANGAN BAHASA EKSPRESIF ANAK USIA 5-6 TAHUN MELALUI METODE KARYAWISATA - Nisa Nurhidayah; Lukman Hamid; Sulistiani Iskandar (al-Urwatul Wutsqo : Jurnal Ilmu Keislaman dan Pendidikan, 2021)
Oral language skills are very important developments in early childhood. One way to optimize expressive language for early childhood can be done using the field trip method. Field trips are an active learning method to observe the world from a direct perspective and the real world. The author uses quantitative research by conducting a pre-experimental design method of type one group pretest-posttest (single group initial test-end test). The results of the pretest and posttest obtained that the average value increased after being given treatment, namely the average pretest was 9.4 while the posttest average was 21,867 with a difference of 12,467. After the field trip the ability to master new vocabulary increased, more courageous in their opinion, as seen before the activity the percentage of children's abilities increased by 9,4% to 21,9%.